2015
DOI: 10.3892/or.2015.4335
|View full text |Cite
|
Sign up to set email alerts
|

Icaritin acts synergistically with epirubicin to suppress bladder cancer growth through inhibition of autophagy

Abstract: Abstract. Bladder cancer is one of the most commonly diagnosed urological malignancies. Acquired resistance to chemotherapy is a great barrier for achieving successful treatment of bladder cancer. In the present study, we investigated the effect and mechanisms of icaritin, a flavonol glycoside derived from genus Epimedium, against human bladder cancer cells. It was found that despite the low cytotoxicity in normal human HEK293 cells, icaritin significantly inhibited the proliferation and colony formation of BT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Routine intravesical instillation with EPI has been widely performed to reduce the recurrence of UC following TUR. Although EPI chemotherapy has achieved an average 16 months of mean disease‐free survival, and suppressed the progression and recurrence in patients with non‐muscle‐invasive UC, acquired resistance to EPI is still a barrier to achieving successful treatment of UC . Some studies with combination treatments have shown antitumor drug action and possible synergistic effects against UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Routine intravesical instillation with EPI has been widely performed to reduce the recurrence of UC following TUR. Although EPI chemotherapy has achieved an average 16 months of mean disease‐free survival, and suppressed the progression and recurrence in patients with non‐muscle‐invasive UC, acquired resistance to EPI is still a barrier to achieving successful treatment of UC . Some studies with combination treatments have shown antitumor drug action and possible synergistic effects against UC.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies with combination treatments have shown antitumor drug action and possible synergistic effects against UC. Ciprofloxacin has been shown to synergistically increase EPI‐induced apoptosis in UC cell lines, and icaritin acts synergistically with EPI to suppress UC cell growth through inhibition of autophagy . However, the molecular mechanisms of EPI in UC remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy is a normal and ubiquitous physiological process that represents an active defensive strategy for external pessimal stimulation (8); it is also an important form of programmed cell death. Autophagy additionally participates in the pathological development of multiple diseases, including malignant tumor types (27).…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, autophagy is beneficial in maintaining a self-stabilized state (8). When there is stress, autophagy may prevent the accumulation of toxic or carcinogenic proteins and organelles and inhibit cellular cancerization (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation